Adenovirus-vectored T cell vaccine for hepacivirus shows reduced effectiveness against a CD8 T cell escape variant in rats. - Alex S Hartlage; Piyush Dravid; Christopher M Walker; Amit Kapoor (PLoS Pathogens)
There is an urgent need for a vaccine to prevent chronic infection by hepatitis C virus (HCV) and its many genetic variants. The first human vaccine trial, using recombinant viral vectors that stimulate pan-genotypic T cell responses against HCV non-structural proteins, failed to demonstrate efficacy despite significant preclinical promise. Understanding the factors that govern HCV T cell vaccine success is necessary for design of improved immunization strategies. Using a rat model of chronic rodent hepacivirus (RHV) infection, we assessed the impact of antigenic variation and immune escape upon success of a conceptually analogous RHV T cell vaccine. Naïve Lewis rats were vaccinated with a recombinant human adenovirus expressing RHV non-structural proteins (NS)3-5B and later challenged with a viral variant containing immune escape mutations within major histocompatibility complex (MHC) class I-restricted epitopes (escape virus). Whereas 7 of 11 (64%) rats cleared infection caused by wild-type RHV, only 3 of 12 (25%) were protected against heterologous challenge with escape virus. Uncontrolled replication of escape virus was associated with durable CD8 T cell responses targeting escaped epitopes alone. In contrast, clearance of escape virus correlated with CD4 T cell helper immunity and maintenance of CD8 T cell responses against intact viral epitopes. Interestingly, clearance of wild-type RHV infection after vaccination conferred enhanced protection against secondary challenge with escape virus. These results demonstrate that the efficacy of an RHV T cell vaccine is reduced when challenge virus contains escape mutations within MHC class I-restricted epitopes and that failure to sustain CD8 T cell responses against intact epitopes likely underlies immune failure in this setting. Further investigation of the immune responses that yield protection against diverse RHV challenges in this model may facilitate design of broadly effective HCV vaccines.